KONFLIK (PERTARUNGAN) BAHASA - Nandang Sarip Hidayat (An-Nida', 2012)
Humans are social beings who will forge interactions with each other, this will lead to language contact, both among internisasi language itself or eksternisasi language different from each other, a language course can lead to conflict, the conflict is not the language that should be blamed because the whole hog can positively impact the birth of the new elements in the language, even just to give birth to new contacts in the language, although on the other hand can cause a negative impact of this language conflicts, can also lead to growth and development and spread of language, it is encouraged because of the social factors culture, religion and politics.